ChemInform Abstract: HBF4‐Catalyzed Nucleophilic Substitutions of Propargylic Alcohols. Issue 14 (March 2016) - Barreiro, Elena; Sanz‐Vidal, Alvaro; Tan, Eric; Lau, Shing‐Hing; Sheppard, Tom D.; Diez‐Gonzalez, Silvia
Abstract: The catalytic activity of aqueous HBF4 in propargylation reactions is presented.